Controlled vocabularies and ontologies in proteomics: Overview, principles and practice - Mayer, Gerhard; Jones, Andrew R.; Binz, Pierre-Alain; Deutsch, Eric W.; Orchard, Sandra; Montecchi-Palazzi, Luisa; Vizcaíno, Juan Antonio; Hermjakob, Henning; Oveillero, David; Julian, Randall; Stephan, Christian; Meyer, Helmut E.; et al. (Biochimica et biophysica acta, 2014)
This paper focuses on the use of controlled vocabularies (CVs) and ontologies especially in the area of proteomics, primarily related to the work of the Proteomics Standards Initiative (PSI). It describes the relevant proteomics standard formats and the ontologies used within them. Software and tools for working with these ontology files are also discussed. The article also examines the “mapping files” used to ensure correct controlled vocabulary terms that are placed within PSI standards and the fulfillment of the MIAPE (Minimum Information about a Proteomics Experiment) requirements. This article is part of a Special Issue entitled: Computational Proteomics in the Post-Identification Era. Guest Editors: Martin Eisenacher and Christian Stephan. ► The semantic annotation using ontologies is a prerequisite for the semantic web. ► The HUPO-PSI defined a set of XML-based standard formats for proteomics. ► These standard formats allow the referencing of CV terms defined in obo files. ► The CV terms can be used to enforce MIAPE compliance of the data files. ► The mass spectrometry CV is constantly maintained in a community process.